Bank Selection Decision: The Choice of Bank among the Customers of Kathmandu District - Tamang, Gopal; Thapa, Bhupal Krishna; Mishra, Sohan Chandra (International Journal of Atharva, 2024)
The customer's choice of bank is an important element of banking strategy in today's increasingly competitive environment. Bank management must identify and improve factors that can increase retention. For commercial banks to plan an appropriate marketing strategy, retain existing customers and attract new customers, they must identify the criteria by which a customer decides to choose a bank. Therefore, the purpose of this study is to investigate the importance of bank selection criteria and to present the most important customer influencing factor in customer bank selection in Kathmandu. Using the answers of 40 customers, quantitative approach is used in the analysis. When conducting the research, a 5-point Likert scale was used to determine the bank's selection criteria. The findings revealed that the main factors determining the choice of a bank by customers are: speed of services, extent of branch network, the location of branches, and influence for sources as major determinants of bank selection among others. On the other hand, price, innovation, financial performance, and electronic banking are the least factors that customers consider when choosing a bank.